The effect of cryotherapy on three dimensional ankle kinematics during a sidestep cutting maneuver - Atnip, B. L.; McCrory, J. L. (Journal of Sports Science & Medicine, 2004)
Although cryotherapy is commonly used in the treatment of acute and chronic athletic injuries, the deleterious effects of limb cooling, such as decreased nerve and muscle function, slowed sensation and inhibition of normal relaxes, may put an athlete at increased risk of additional injury. The purpose of this study was to determine the effects of cryotherapy on subtalar and ankle joint kinematics of healthy athletes performing a sidestep 45° cut. We hypothesized that greater joint displacements and velocities would be seen after icing. Twenty one subjects performed a 45° sidestep cut prior to and after limb cooling. Retroreflective markers were placed on the subject's shank and foot while 6 high-speed cameras were used to collect the kinematic data. In this test-retest controlled laboratory study, a repeated measures ANOVA was performed on the PRE and POST icing data for the minimum and maximum joint displacements and velocities. No statistical differences were noted between the PRE and POST icing conditions. The results indicate that a 10-minute icing treatment did not have an effect on either the movement patterns or angular velocities. Our results do not support any change in practice of icing injured ankles for ten minutes during halftime of athletic events.